Progress in research and technological developments of phase change materials integrated photovoltaic thermal systems: The allied problems and their mitigation strategies - Rajamony R.K.; B. K.; Lagari I.A.; Paw J.K.S.; Sofiah A.G.N.; Suraparaju S.K.; Pandey A.K.; Samykano M.; Soudagar M.E.M.; Khan T.M.Y. (Elsevier B.V., 2025)
The efficiency of solar cells and photovoltaic (PV) panels are lacking significantly due to its surface overheating by the incident solar radiation. Indeed, the generated heat energy is harnessed by integrating a thermal system into PV panel, which introduces a photovoltaic thermal (PVT) system. Phase change materials (PCM)s are a class of energy material that is intended to facilitate thermal regulations of photovoltaic (PV) panel. Despite, PVT systems are allied with numerous problems like, integration technique, increase in overall weight of the system, dust accumulation, complication of tracking etc., which are of utmost importance to be resolved. The foremost aim of the review is to analyze the current technologies and allied problems of PVT system, the impact of the overall weight of the system on the PVT systems, detailed assessment of recent advancements in soil mitigation techniques, and the economic benefit of the PVT systems. Also, this review article is specifically intended to discuss on a) concerns allied with PV and PVT system integrated with PCM for thermal regulation; b) framework intimidating the performance of PCM-integrated PVT system; and c) mitigation techniques to resolve the problems and enhanced the performance of PCM integrated PVT system. A elaborative technical exploration on common issues associated with both PV and PVT systems in terms of surface cleaning towards dust mitigation via advanced mechanisms and futuristic technologies is comprehensively presented. A new possible sustainable solution towards enhancing the performance of PV and PVT systems is also provided. A summary of numerous research works conducted on enhancing the performance of PVT system integrated with PCM at different global locations is summarized. Furthermore, this review also discusses the economic analysis of PVT system integrated with PCM along with a summary of technical challenges and future outlook of PCM integrated PVT system to boost sustainable development. ? 2023